2023
DOI: 10.3390/polym15122674
|View full text |Cite
|
Sign up to set email alerts
|

Designing Electrical Stimulation Platforms for Neural Cell Cultivation Using Poly(aniline): Camphorsulfonic Acid

Abstract: Electrical stimulation is a powerful strategy to improve the differentiation of neural stem cells into neurons. Such an approach can be implemented, in association with biomaterials and nanotechnology, for the development of new therapies for neurological diseases, including direct cell transplantation and the development of platforms for drug screening and disease progression evaluation. Poly(aniline):camphorsulfonic acid (PANI:CSA) is one of the most well-studied electroconductive polymers, capable of direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that neuronal differentiation, both of MSCs and NSCs, can be achieved by electrical stimulation [5,[28][29][30]; as well as it is possible to influence the neural lineage of differentiated NSCs through the electrical stimulation [7]. Responsible for the response to electrical stimulation are the voltage-gated calcium channels [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that neuronal differentiation, both of MSCs and NSCs, can be achieved by electrical stimulation [5,[28][29][30]; as well as it is possible to influence the neural lineage of differentiated NSCs through the electrical stimulation [7]. Responsible for the response to electrical stimulation are the voltage-gated calcium channels [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Organ regeneration involves careful regulation of cell division, movement, and positioning. During the embryogenesis, electrical signals serve to direct the formation of organs and limbs [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations